Pemanfaatan Stylus Pen dengan Microsoft Onenote Menggunakan Model Discovery Learning untuk Meningkatkan Hasil Belajar pada Materi Sistem Reproduksi - Riska Ramadanti; Meilinda Meilinda (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This study aims to determine the effect of use Stylus Pen with Microsoft Onenote on student learning outcomes on the subject matter of the reproductive system. This research is a classroom action research. The subjects in this study were 30 students from class XI MIA 1 SMAN 10 Palembang. This research process consists of two cycles, namely Cycle 1 and Cycle 2. Each cycle consists of two meetings. Implementation of the action using the learning model Discovery Learning. In the pre-cycle stage, it can be seen that the average completeness value is 47.8, which is still below the minimum completeness, which is 72.00, so it is important to make improvements. In cycle I, the average score of completeness touched 85 and experienced an increase in mastery to 92.3 in cycle II, which met the minimum score of completeness. Based on the results of this study it can be seen that the use Stylus Pen with application Microsoft Onenote can improve student learning outcomes in the material of the reproductive system. The results of this study can be used as reference material for teachers and prospective educators to identify appropriate learning media to improve learning outcomes.